Characteristics of oil based muds and influence on the environment - Jamrozik, Aleksandra; Protasova, Evgenia; Gonet, Andrzej; Bilstad, Torleiv; Żurek, Roman (My University, 2016)
Oil based muds (OBM) are highly important in well drilling. Water based muds (WBM) and synthetic based muds are not providing sufficient qualities in fulfilling all of the functions of OBM. OBMs ensure more efficient drilling but also disadvantages such as higher initial cost, more stringent pollution controls and reduced effectiveness of some logging tools. Expenses for mud are reaching 10–15% of total well cost. However, high costs are still low compared to expenses for corrective measures in the case of using mud with poor properties, which could lead to drilling disruption as well as excessive time and cost. OBM and cuttings are saturated with toxic compounds and if discharging to sea poses ecological threats. Perhaps the most hazardous oil component for aquatic organisms are low-boiling aromatics, which consist of benzenes and naphthalenes both soluble in water. Additionally, the higher-boiling aromatic fractions are of high environmental interest due to their persistence in sediments, leading to enzyme induction, cellular dysfunctions, genetic alterations, and chronic effects on organisms. There is a difference in volume of generated waste between using water- and oil-based muds. WBM produces 7,000–13,000 bbl of waste per well. Depending on well depth and diameter 1,400–2,800 bbl are drill cuttings. OBM generates mush less waste as the mud is usually recycled and only drill cuttings with volumes of 2,000–8,000 bbl per well need treatment prior discharge. This paper discusses the hazardous effect of toxic compounds in OBM and evaluates the efficiency of different OBM treatment towards zero discharge.
AGH Drilling, Oil, Gas
Keywords: oil based muds; drilling waste; toxicity